Resolving war-induced interpersonal conflicts in the corporate environme: кваліфікаційна робота - Petrov, Sergii Gennadiyovich; Петров, Сергій Геннадійович (Університет «КРОК», 2024)
The diploma project of S. G. Petrov, dedicated to the topic "Resolving interpersonal conflicts in the corporate environment caused by the war in Ukraine", impresses with its relevance and depth of research. The author carefully analyzed the impact of the military conflict on internal relations in organizations and identified the main factors that lead to interpersonal conflicts in peacetime and under martial law. The diploma project is distinguished not only by its thematic relevance, but also by a complete and systematic approach to the study of the problem. The author successfully combined theoretical foundations with practical aspects, revealing important nuances of resolving interpersonal conflicts in wartime conditions. Particularly important is the section "Pri ority directions and proposals for resolving interpersonal conflicts based on mediation skills." The author studied existing theoretical approaches and implemented them in the context of domestic business, which indicates a deep understanding and analysis of the subject area. The use of the conflict resolution algorithm and recommendations for its implementation are also a positive contribution to the work. This provides a practical focus and realizable opportunities to implement the obtained results in a real business environment. The general conclusion of the diploma project testifies to the author's high level of professional competence and his ability to apply theoretical knowledge to solve actual problems in practice. The work is a significant contribution to the study and optimization of management practices of Ukrainian enterprises in the difficult condi tions of the military conflict. It is important to emphasize that the recommendations and strategies, brought to the fore, can serve as a basis for further research and development of interpersonal conflict resolution practices in the organizational environment. In gen eral, this diploma project is an important contribution to understanding and solving problems arising in the context of the military conflict in Ukraine. Its high level of academic and practical value causes confidence in the possibility of using its results to further improve management processes and create a healthy organizational climate.
Keywords: медіація